Redox imbalance in infertility and assisted reproduction: biomarkers, mechanisms, multi-omics integration, and personalised therapeutic strategies - Braulio Peramo; Divyesh Upadhyay; Linda Bouhafs; Habiba Alsafar (Frontiers in Medicine, 2026)
Redox biology occupies a central but paradoxical role in human reproduction. Reactive oxygen species (ROS) are indispensable mediators of sperm capacitation, oocyte activation, embryo development, and trophoblast invasion, yet excessive ROS generation causes oxidative stress that damages gametes, impairs preimplantation development, and compromises implantation. Conversely, reductive stress, an emerging but still underappreciated state in which antioxidant defences exceed physiological need, may suppress the low-level ROS signalling required for normal reproductive function. Despite decades of mechanistic research, clinical translation has been limited by the absence of standardised redox phenotyping and by the widespread use of empirical antioxidant supplementation, the benefits of which remain unproven in adequately powered randomised controlled trials. This review synthesises current evidence on the dual-pole redox continuum in infertility and assisted reproductive technology, with emphasis on the mechanistic pathways through which oxidative and reductive stress affect male reproductive function, ovarian and oocyte competence, endometrial receptivity, and preimplantation embryo development. It also critically examines the clinical failure of non-stratified antioxidant trials and evaluates the diagnostic potential of redox biomarkers and multi-omics approaches, including oxidation–reduction potential measurement, metabolomics, transcriptomics, and proteomics, for patient-level phenotyping. Collectively, the available evidence suggests that oxidative and reductive stress operate through mechanistically distinct but clinically overlapping pathways, and that empirical supplementation of heterogeneous, uncharacterised populations has not consistently improved live birth outcomes in adequately powered trials. Multiple co-existing factors, including aetiological heterogeneity, inconsistent dosing and timing, variable baseline nutritional status, methodological limitations of the included RCTs, and the absence of pre-treatment redox phenotyping, likely account for this translational gap. A tiered, biomarker-guided framework is proposed as a conceptually grounded route towards personalised redox management in reproductive medicine, pending validation in prospective stratified trials. Standardisation of redox assays, establishment of compartment-specific reference ranges, and the conduct of adequately powered stratified randomised controlled trials should be prioritised to move the field beyond empirical supplementation towards evidence-based precision redox therapeutics.